Spectrophotometric Determination of Olanzapine in Pharmaceutical Preparations - Siva Prasad, K.V.; Rajendra Kumar, J.M.; Reddy, M.V.V.N.; Prabhakar, G.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods (method A and B) have been described for the assay of olanzapine (OLP) in pure form and in pharmaceutical formulations. These methods are based on the oxidation followed by complexation between OLP and o-phenanthroline or potassium ferricyanide in presence of ferric chloride to form a coloured product with λmax at 520 nm for method A and 760 run for method B respectively. Beer's law limits, precision and accuracy of these methods are checked by the UV reference method. The results obtained are reproducible and are statistically validated and so found to be suitable for the assay of OLP in bulk and pharmaceutical formulations.